Implementation of Noble Values Assessment in Improving the Religious Character of Class X Students of SMK Negeri 2 Samarinda - Taufik, Mokhamad; Zurqoni, Zurqoni; Rusdi, Rusdi; Al Faruqi, Muhammad Qori (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aims to describe the implementation of noble value assessments in shaping the religious character of 10th-grade students at SMK Negeri 2 Samarinda. Method: Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. Results: The findings reveal that religious character assessment is conducted using instruments such as daily journals, attitude assessment rubrics, and student reflections. The main assessed indicators include honesty, responsibility, and discipline in worship. Although the implementation has shown positive results, there are several challenges, including limited instruments, inadequate teacher training, and an inconsistent school culture. The study concludes that noble value assessment is effective in forming religious character when conducted systematically and supported by all school components. Novelty: The novelty of this study lies in its practical analysis of noble value assessments as a means of shaping religious character within a vocational high school context—a setting rarely explored in moral education research. By focusing on specific instruments like journals, rubrics, and reflections, and highlighting key indicators such as honesty, responsibility, and worship discipline, the study moves beyond theoretical discourse to reveal concrete implementation practices. It also addresses systemic challenges, offering a contextualized insight into how value-based assessment can function effectively when integrated into the fabric of school life.